CAX and Xsel: a software bundle to aid in automating NAA spectrum analysis - Guilherme Soares Zahn; Lucas Stano Junqueira; Frederico Antonio Genezini (Brazilian Journal of Radiation Sciences)
In this work, the scripting capabilities of Genie-2000 were used to develop a software (CAX) that automatically analyses all spectrum files in either Ortec's CHN or Canberra's MCA or CNF formats in a folder, generating two output files: a print-ready text file (.DAT) and a Comma-Separated Values (.CSV) file which can be easily imported in any major spreadsheet software. A second tool, named Xsel, consists in an Excel spreadsheet which automatically identifies the spectrum lines associated with the elements of interest, generating a clean output sheet which can be easily imported in a general spreadsheet that calculates the concentrations; an important addition to this spreadsheet is the ability to automatically recalibrate each spectrum, increasing the reliability of the peak identification procedure. These software are already used in daily routines in IPEN's Neutron Activation Laboratory, greatly reducing the time required for sample analyses, as well as reducing the possibility of transcription errors.